MRSA dan VRSA pada Paramedis RSUD Ratu Zalecha Martapura - Ratih Dewi Dwiyanti; Akhmad Muhlisin; Akhmad Muntaha (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2015)
Abstact: Staphylococcus aureus strains isolated from hospital generally been resistant to many antimicrobial-resistant strains of Staphylococcus aureus to vancomycin was rarely reported. Strains of Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of nosocomial infections that are multiresistant to antibiotics. This study aims to determine the presence of bacteria Methicillin-resistant Staphylococcus aureus (MRSA) and Vancomycin resistant Staphylococcus aureus (VRSA) on paramedics in the treatment room and the surgical ICU care hospitals Zalecha Martapura queen. This study used a descriptive survey method. The population in this study were nurses who worked in the surgical and ICU care that numbered 38 people. Sampling technique accidental sampling with a sample of 27 people. The survey results revealed 27 positive samples of Staphylococcus aureus 14 people, there is a sensitivity test results of 7 samples were resistant to cefoxitin (MRSA 26%), 4 samples were resistant to oxacilin and 7 samples were resistant to vancomycin (VRSA 26%). Concluded there is MRSA and VRSA in hospital Queen zalecha Martapura, it is advisable to increase the cleanliness of individuals and the use of personal protective equipment to reduce the incidence of nosocomial infections in the scope of the hospital.